Validity and reliability of the Persian version of the Adverse Childhood Experiences Abuse Short Form - Maryam Chegeni; Aliakbar Haghdoost; Mahin Eslami Shahrbabaki; Parvin Mangolian Shahrbabaki; Nouzar Nakhaee (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND AND AIM: Measuring child abuse and adverse experiences is a critical task with regard to its long-term impact on the health of individuals and communities. The purpose of this study was to validate the Persian version of the International Adverse Childhood Experiences Abuse Short Form (ACE-ASF) in Iranian society. MATERIALS AND METHODS: This cross-sectional study was conducted in Kerman, southeast of Iran, in 2019, on 494 students from Kerman University of Medical Sciences, selected by convenience sampling method. Psychometric properties of the questionnaire were examined after the forward and backward translation processes. The factor structure of the questionnaire was evaluated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The concurrent validity of the questionnaire was assessed using the childhood trauma questionnaire (CTQ). Cronbach's alpha and corrected item-total correlation were used to measure reliability. RESULTS: The mean age of participants was 24.3 ± 5.3 years. Based on EFA, two physical-emotional abuse and sexual abuse factors were obtained. The CFA fit indices well supported two extracted factors. The CFA showed acceptable factor loadings. The internal consistency coefficient of Cronbach's alpha was 0.75 for the physical-emotional abuse factor and 0.77 for the sexual abuse factor. The correlation coefficient of ACE-ASF and CTQ was r = 0.56. The reliability index of intraclass correlation coefficient was 0.73 (95% confidence interval: 0.60-0.84). CONCLUSION: The Persian version of the ACE-ASF questionnaire has acceptable psychometric properties.